Assessing the anthropogenic disturbance impact on migratory and resident shorebirds in sandy beaches of the São Paulo, Brazil Coast - Esparza, Karina Anahí Ávila [UNESP]; Lima, Bruno [UNESP]; Barbieri, Edison (Springer Nature, 2025)
Coastal ecosystems are critical for biodiversity, yet they face increasing threats from human activities, particularly for migratory shorebirds that depend on these habitats for survival. Shorebirds are highly sensitive to environmental changes, with habitat degradation and anthropogenic disturbances significantly impacting their populations, especially during non-breeding periods in tropical and subtropical regions. While studies have documented these effects globally, regional assessments in understudied areas, such as the Brazilian coast, remain scarce. Here, we evaluate the impact of anthropogenic disturbance on the diversity and abundance of migratory and resident shorebirds along sandy beaches in São Paulo, Brazil. We show that less disturbed beaches, such as Praia do Tanigwá, support higher species richness and abundance, particularly for dominant species like the semipalmated plover (Charadrius semipalmatus), compared to heavily urbanized areas. In contrast, beaches with high human activity exhibited reduced bird diversity and altered behavior, emphasizing the detrimental effects of unregulated recreation and urbanization. These findings contrast with previous assumptions that all coastal habitats in the region are equally critical for shorebirds, revealing instead that localized conservation efforts are essential. Our results highlight the urgent need for targeted management strategies to mitigate human impacts, ensuring the preservation of key stopover sites for migratory shorebirds in rapidly developing coastal zones.